Conflicts of norms and conflicts of jurisdictions : the relationship between the WTO agreements and the MEAs and other treaties - Marceau, Gabrielle (2001)
Suggests that the issue of the relationship between the WTO Agreement and other treaties can only be appreciated when distinguishing between the normative and jurisdictional dimensions of that matter.